Brainstem raphe hypoechogenicity is an independent predictor of post-stroke depression - Richter, Daniel; Ebert, Andreas; Mazul, Lisa; Ruland, Quirin; Charles James, Jeyanthan; Gold, Ralf; Tsivgoulis, Georgios; Palaiodimou, Lina; Juckel, Georg; Krogias, Christos (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Post-stroke depression (PSD) is a common complication after stroke and has a substantial effect on the quality of life of patients. Nevertheless, reliable individual prediction of PSD is not possible. As depressive symptoms have been associated with brainstem raphe (BR) hypoechogenicity on transcranial sonography (TCS), we aimed to explore the association of BR hypoechogenicity and the occurrence of PSD.The Prognostic Markers of Post-Stroke Depression (PROMoSD) study is a prospective, observational, single-center, investigator-initiated study that included patients with acute ischemic stroke (AIS) to investigate the presence of BR hypoechogenicity by TCS early after symptom onset. The primary outcome was the presence of PSD assessed at the three-month follow-up investigation by a blinded psychiatrist and defined according to the fifth version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V criteria).From 105 included AIS patients, 99 patients completed the study. AIS patients with a hypoechogenic BR developed a PSD at three months more frequently compared to patients with normal echogenicity (48.0% versus 4.1%, P <0.001). After adjustment for confounders (sex, mRS at follow-up, previous depressive episode), a hypoechogenic BR remained independently associated with a substantial increase in the appearance of PSD (adjusted OR: 6.371, 95%-CI: 1.181–34.362).A hypoechogenic BR is a strong and independent predictor of PSD at three months after AIS. TCS could be a routine tool to assess PSD risk in clinical practice, thereby streamlining diagnostic and therapeutic algorithms.
Keywords: Post-stroke depression; Brainstem raphe; TCS; Sonography